2006
DOI: 10.1158/1078-0432.ccr-05-1907
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Beam Therapy Overcomes the Radiation Resistance of Uterine Cervical Cancer Originating from Hypoxia

Abstract: Purpose: High linear energy transfer (LET) particles are believed to decrease tumor radiation resistance originating from hypoxia. However, no proof of this effect has been provided by clinical trials and related clinical research. Hence, we investigated the radiation biological aspects of high LETcarbon beam therapy on cervical cancer. Experimental Design: This study involved 49 patients with stage IIIb bulky and stage IVa cervical cancer treated with high LETcarbon beams between October 1995 and June 2000. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 28 publications
6
76
0
Order By: Relevance
“…High LET radiation could overcome such radioresistance because of its diminished susceptibility to the OER effect. In a clinical trial of high LET carbon ion beam, Nakano et al compared its efficacy against hypoxic and normoxic cervical tumors and showed similar disease-free survival between hypoxic (<20 mmHg) and oxygenated (>20 mmHg) tumors suggesting that high LET radiation can overcome the radioresistance caused by tumor hypoxia [90]. Modeling analysis, however, suggest that the reduction of OER with high LET radiation under the clinical tumor hypoxic environment (0.5-20 mmHg) is relatively moderate with approximately 15% benefit over photon [85].…”
Section: Effect Of Cell Cycle and Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…High LET radiation could overcome such radioresistance because of its diminished susceptibility to the OER effect. In a clinical trial of high LET carbon ion beam, Nakano et al compared its efficacy against hypoxic and normoxic cervical tumors and showed similar disease-free survival between hypoxic (<20 mmHg) and oxygenated (>20 mmHg) tumors suggesting that high LET radiation can overcome the radioresistance caused by tumor hypoxia [90]. Modeling analysis, however, suggest that the reduction of OER with high LET radiation under the clinical tumor hypoxic environment (0.5-20 mmHg) is relatively moderate with approximately 15% benefit over photon [85].…”
Section: Effect Of Cell Cycle and Oxygenationmentioning
confidence: 99%
“…The same model was also used to find that the RBE of two other alpha particle emitters, 148 Gd and 223 Ra, is 7.4 ± 2.4 and 5.4 ± 0.9, respectively [39]. In addition, in vivo studies of alpha emitter 213 Bi labeled peptide found an RBE of 2-3 for control of colon cancer and surprisingly close to 1.0 for marrow toxicity using beta emitter 90 Y labeled peptide as reference [40,41]. Nayak et al found similar RBE of 3.4 for 213 Bi labeled DOTATOC when treating pancreatic adenocarcinoma cells using 137 Cs as reference radiation [42].…”
mentioning
confidence: 98%
“…In comparison to photon based treatment techniques, protons have the potential to further reduce doses to OAR [19,28]. Small series of cervix cancer patients have been treated with carbon ions [12,22] and for a small number of patients protons were used as a boost modality [15].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to photon based treatment techniques, protons have the potential to further reduce doses to OAR [19,28]. Small series of cervix cancer patients have been treated with carbon ions [12,22] and for a small number of patients protons were used as a boost modality [15].The aim of this study was to evaluate the potential benefit of proton beam therapy compared to standard conformal photon therapy as well as intensity modulated photon beam therapy (IMXT) for locally advanced cervix cancer. For proton beam therapy we considered two options.…”
mentioning
confidence: 99%
“…It was reported that Bcl-2-overexpressing HeLa cells are more resistant to γ-rays (0.2 keV/µm) and helium ions (16.2 keV/µm) than neomycin resistance geneexpressing HeLa cells, whereas heavy ions (76.3-1610 keV/µm) yield similar survival regardless of Bcl-2 overexpression. This implies that heavy-ion radiotherapy may be equally effective against CSCs (64) and that carbon ion beam radiotherapy may not induce CSC repopulation in contrast to X-ray radiotherapy.…”
Section: Radiotherapy: the Potential Of Carbon Ion Beam Therapy In Rementioning
confidence: 99%